Dynamic variation in second language acquisition: A language processing perspective, Bronwen Patricia Dyson, John Benjamins Publishing Company (2021). 274 - Rudi Suherman (JOALL (Journal of Applied Linguistics and Literature), 2023)
Arguably, second language acquisition has always been an interesting topic to discuss, proven by many existing theories that play an essential role and contribute to this field's advancement and proliferation. Among many are Processability Theory (PT), a prominent theory of L2 development and processing theory that predicts well-ordered, cross-linguistically valid stages in second language acquisition and provides language-specific predictions covering developmental and variational stages dimensions (Pienemann, 1998, 2005, 2015). It accounts for explicit prediction of the language elements in which L2 learners learn to process different morphological and syntactical structures productively regardless of their backgrounds.